Heterosexism, Depression, and Campus Engagement Among LGBTQ College Students: Intersectional Differences and Opportunities for Healing. Issue 8 (3rd July 2017) - Kulick, Alex; Wernick, Laura J.; Woodford, Michael R.; Renn, Kristen
ABSTRACT: LGBTQ people experience health disparities related to multilevel processes of sexual and gender marginalization, and intersections with racism can compound these challenges for LGBTQ people of color. Although community engagement may be protective for mental health broadly and for LGBTQ communities in buffering against heterosexism, little research has been conducted on the racialized dynamics of these processes among LGBTQ communities. This study analyzes cross-sectional survey data collected among a diverse sample of LGBTQ college students ( n  = 460), which was split by racial status. Linear regression models were used to test main effects of interpersonal heterosexism and engagement with campus organizations on depression, as well as moderating effects of campus engagement. For White LGBTQ students, engaging in student leadership appears to weaken the heterosexism–depression link—specifically, the experience of interpersonal microaggressions. For LGBTQ students of color, engaging in LGBTQ-specific spaces can strengthen the association between sexual orientation victimization and depression.